1980
DOI: 10.1093/brain/103.3.603
|View full text |Cite
|
Sign up to set email alerts
|

Gliomatous Transformation and Demyelinating Diseases

Abstract: The clinical and pathological details are described of three patients with demyelinating diseases associated with a glioma, the effects of which proved fatal. The findings suggest that the tumours developed from neoplastic transformation of glia in areas of established demyelination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Previous studies have focused on the possible associations between MS and CNS tumours, 16,18 bladder cancers, 16 cancers of the haematopoitic and lymphatic system, 12-14 breast cancers 15,16 and nasopharyngeal cancers. 16 In our study, the observed number of CNS tumours, bladder cancers and haematopoietic-lymphatic malignancies did not exceed the expected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have focused on the possible associations between MS and CNS tumours, 16,18 bladder cancers, 16 cancers of the haematopoitic and lymphatic system, 12-14 breast cancers 15,16 and nasopharyngeal cancers. 16 In our study, the observed number of CNS tumours, bladder cancers and haematopoietic-lymphatic malignancies did not exceed the expected.…”
Section: Discussionmentioning
confidence: 99%
“…Ratios of the incidence of breast cancer in women with MS to that in women without MS served as measure of the relative risk (RR). Analyses were carried out using the proc GENMOD procedure in SAS, and adjustment was made for age (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) , . .…”
Section: Registersmentioning
confidence: 99%
See 1 more Smart Citation
“…Opinion is divided about whether the rare concurrence of multiple sclerosis and glioma is explained by cause and effect or coincidence 15,23 . If gliomas in patients with multiple sclerosis are more likely to be multicentric, then the hypothesis of cause and effect could be supported.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports on the co-existence of multiple sclero sis and glioma have been published [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], Usually, the demyelinating disorder has been the presenting illness, and the glioma developed after intervals from 16 months to 28 years. MS has, however, in most cases run a benign course.…”
Section: Discussionmentioning
confidence: 99%